HUBUNGAN PAPARAN KONTEN PRENATAL JOURNEY DENGAN TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG PERSIAPAN KEHAMILAN SEHAT DI UNIVERSITAS MUHAMMADIYAH SUMATERA BARAT - Liza Andriani; Rantih Fadhlya Adri; Lisa Ernita; Leni Reskina; Mira Hastuti; Serly Agustin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Exposure to health information through social media continues to increase and plays an important role in shaping adolescent girls’ knowledge, particularly regarding preparation for a healthy pregnancy during the preconception period. One of the widely accessed contents is Prenatal Journey, which presents pregnancy experiences and preparation for motherhood. This study aimed to determine the relationship between exposure to Prenatal Journey content on social media and the level of knowledge of adolescent girls regarding healthy pregnancy preparation at Universitas Muhammadiyah Sumatera Barat. This study employed an observational design with a cross-sectional approach. The study was conducted at Universitas Muhammadiyah Sumatera Barat. The population consisted of 100 adolescent girls, with a sample of 50 respondents selected using proportional random sampling. The results showed that most respondents had low exposure to Prenatal Journey content, amounting to 26 respondents (52%), while the majority of respondents had a high level of knowledge regarding healthy pregnancy preparation, totaling 35 respondents (70%). Statistical analysis using the Chi-square test indicated a significant relationship between exposure to Prenatal Journey content on social media and the level of knowledge of adolescent girls regarding healthy pregnancy preparation, with a p-value of 0.000 (p 0.05). The findings of this study are expected to serve as a reference for health professionals and educational institutions in utilizing social media as an effective medium for reproductive health education among adolescents, particularly in improving readiness for a healthy pregnancy from an early age.Keywords: conten exposure, prenatal journey, knowledge, adolescent girls, healthy pregnancy preparation